2018
DOI: 10.3389/fpls.2018.01242
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Metabolism, Photosystem II, and Fatty Acid Composition of Two Tall Fescue Genotypes With Different Heat Tolerance Under High Temperature Stress

Abstract: Tall fescue (Festuca arundinacea Schreb.) is a typical and widely used cool-season turf grass. High temperature is a key factor that limits its utility. The objectives of this study were to investigate the behaviors of fatty acid composition and its gene expression patterns in heat-resistant genotype “TF71” and heat-sensitive genotype “TF133” exposed to heat stress (40/35°C, 14/10 h), and to broaden our comprehension about the relationship between heat tolerance and fatty acid function. The result showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 59 publications
4
27
0
Order By: Relevance
“…The membrane stability of most alfalfa cultivars was significantly affected by heat stress, which may reveal the heat sensitivity of the cultivars. Our results were in agreement with the findings of Kumar et al [32] in chickpea, Sita et al [30] in lentil, and Hu et al [21] in tall fescue, who reported higher EL under heat stress. The increase in lipid peroxidation might be as a result of the overproduction and accumulation of ROS, which then causes membrane peroxidation, protein degradation, and DNA damage to severely inhibit growth [33][34][35].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The membrane stability of most alfalfa cultivars was significantly affected by heat stress, which may reveal the heat sensitivity of the cultivars. Our results were in agreement with the findings of Kumar et al [32] in chickpea, Sita et al [30] in lentil, and Hu et al [21] in tall fescue, who reported higher EL under heat stress. The increase in lipid peroxidation might be as a result of the overproduction and accumulation of ROS, which then causes membrane peroxidation, protein degradation, and DNA damage to severely inhibit growth [33][34][35].…”
Section: Discussionsupporting
confidence: 94%
“…Another heat sensitive cultivar (Gibraltar) showed a significant reduction in PI ABS . A similar result was reported in tall fescue under heat stress [21]. In addition, Fahad et al [29] reported a significant reduction in the photosynthetic activities of two rice cultivars under high day and night temperatures.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations